Nuclear localization of dengue virus capsid protein is required for DAXX interaction and apoptosis - Netsawang J. (2014)
Dengue virus capsid protein (DENVC) localizes to both the cytoplasm and nucleus of dengue virus-infected cells. DENV C contains three nuclear localization signals (NLS), 6KKAR9, 73KKSK76, and the bipartite signal 85RKeigrmlnilnRRRR100. Stable HepG2 cells constitutively expressing DENV C, DENV C (Δ85-100) and DENV C (Δ73-100) were constructed to clarify whether nuclear translocation of DENV C affected apoptosis in liver cell line. While the wild-type DENV C could translocate into the nuclei of HepG2 cells, the mutant DENV Cs were restricted to the cytoplasm. The loss of nuclear localization of both mutant DENV Cs resulted in the disruption of their interactions with the apoptotic protein Daxx. Interestingly, upon treatment with anti-Fas antibody, the HepG2 cells expressing the wild-type DENV C showed significantly more apoptosis compared with the HepG2 cells expressing either mutant DENV C. To identify the amino acids required for DAXX interaction and apoptosis, substitution mutations either (K73A/K74A) or (R85A/K86A) were introduced into the C-terminal region of DENV C, and tested whether these mutations affected its interaction with Daxx and apoptosis. The results demonstrate that 73KK and 85RK of DENV C are important for its nuclear localization, interaction with DAXX and induction of apoptosis. This work is the first to demonstrate that nuclear localization of DENV C is required for DAXX interaction and apoptosis. © 2009 Elsevier B.V. All rights reserved.